Development of Pop Up Book Media Material Distinguishing Characteristics of Healthy and Unfit Environments Class III Students Elementary School - Permana, Erwin Putera; Sari, Yeny Endah Purnama (Universitas Pendidikan Ganesha, 2018)
This research is based on the observation in the third grade of Natural Science (IPA) subject matter of healthy and unhealthy environment characteristic, that most of students have difficulty in learning because the teacher uses conventional teaching method. In addition, the use of learning media is considered less maximized by teachers. This research is research and development (R & D) with model of ADDIE development. Stages there are 5 stages namely 1) Analysis (Analysis), Development (Design), Implementation (Implementation), Evaluation (Evaluation). Validation is done by material experts, media experts, and classroom teachers. The conclusion of this research is (1) Result of Development of Pop Up Book media with material to distinguish the characteristics of healthy and unhealthy environment Valid. (2) The teacher's response to the learning media of Pop Up Book that was developed, after being used in learning material, characteristic of healthy and unhealthy environment obtained good response. Likewise the response of students to this media get a positive response. (3) Pop Up Book media characteristics of a healthy and unhealthy environment based on the overall assessment of the percentage of assessment is in the category of very appropriate to be used as a medium of learning Natural Science for grade 3 primary school students. Based on the conclusions of this study, recommended: (1) for teachers, one of the media that can be used in supporting the learning process is Pop Up Book, can help students become more active and can create a fun class atmosphere. (2) For further research, trials should be conducted more widely, so as to produce a widely used learning medium.